Rebekah : a novel - Smith, Jill Eileen, 1958- (Smith, Jill Eileen, 1958- Wives of the patriarchs, 2013)
When her father dies and she is left in the care of her conniving brother Laban, Rebekah knows her life has changed forever. Her hope for the future is restored when she falls in love with her cousin Isaac, and their relationship starts strong. But marital bliss cannot last forever, and the birth of their twin sons marks the beginning of years of misunderstanding, disagreement, and betrayal. The rift between them grows wider and wider until it is surely too deep to be mended. And yet, with God all things are possible.